Fiber-reinforced ultrahigh-temperature ceramic-based composite material and preparation method thereof
In the preparation of fiber-reinforced ultra-high temperature ceramic matrix composite materials, the use of slurry and ultrasonic vibration treatment technology of water-soluble polymer dispersant is solved, and efficient and uniform introduction of ceramic matrix and material performance are achieved.
Patent Information
- Application Number
- CN202411963291.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the prior art, when preparing fiber-reinforced ultra-high temperature ceramic matrix composites, the ceramic matrix content is low and the process cycle is long, which affects the material performance.
Using water-soluble polymer as the dispersant, the ultra-high temperature ceramic powder is mixed with the solvent to form a slurry with a solid content of 25 to 45 vol%. After wet ball milling, magnetic stirring, vacuum slurry impregnation and ultrasonic vibration treatment, it is then immersed in the ceramic precursor for pressurized impregnation and ultrasonic vibration, and finally curing and cracking to obtain a densified fiber-reinforced ultra-high temperature ceramic matrix composite.
Through this process, the ceramic content and material properties are improved, the process flow is simplified, the process cycle is shortened, and the problems of low efficiency and long cycle of ceramic powder introduction in traditional processes are solved.
Smart Images

Figure CN119751103A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fiber-reinforced ultra-high temperature ceramic-based composite material and a preparation method thereof, belonging to the technical field of ultra-high temperature ceramics. Background Art
[0002] Ultra-high temperature ceramics (UHTCs) mainly refer to borides, carbides or nitrides of early transition metals of the IVB and VB subgroups in the periodic table, such as ZrB2, ZrC, HfB2, HfC, TaC, etc., which have extremely high melting points (>3000℃) and good oxidation resistance and ablation resistance. Their ability to maintain a non-ablative state for a long time in ultra-high temperature and strong oxidation environments makes them a very valuable and promising class of non-ablative thermal protection materials.
[0003] However, the inherent brittleness and low damage tolerance of ultra-high temperature ceramic materials seriously affect their practical wide application. In order to improve the mechanical properties and damage tolerance of UHTCs, many methods have been proposed, such as particle reinforcement, whisker reinforcement, graphite sheet reinforcement, short carbon fiber reinforcement and continuous carbon fiber reinforcement. Among these toughening and strengthening methods, continuous carbon fiber reinforcement is used to form fiber-reinforced ultra-high temperature ceramic matrix composites (C f / UHTCs) is the most effective way to overcome the inherent brittleness of UHTCs; this continuous carbon fiber reinforced ultrahigh temperature ceramic composite has a continuous carbon fiber skeleton, which can maximize the toughening effect of carbon fiber. However, while improving the toughness of UHTCs, its staggered carbon fiber skeleton also hinders the close integration of UHTCs and carbon fiber preforms, resulting in insufficient UHTCs content and affecting performance. Therefore, how to efficiently introduce ultrahigh temperature ceramics into continuous carbon fiber preforms to obtain high-performance composites has become one of the most severe challenges in recent years.
[0004] C f The preparation processes of UHTCs include slurry infiltration (SI), chemical vapor infiltration (CVI), reactive melt infiltration (RMI) and organic precursor impregnation-pyrolysis (PIP). The above processes have their own process adaptability characteristics, and a single process has certain limitations. In the SI process, UHTCs are introduced into the carbon fiber preform in the form of particles. Due to the interlaced structure of the preform and the friction between the particles, it is easy to cause blockage on the surface of the carbon fiber preform, resulting in insufficient UHTCs content and uneven distribution inside the preform. In the CVI process, the deposition product is prone to form preferentially on the surface of the preform, prematurely closing the surface pores and hindering further densification inside the preform. Therefore, this process is more suitable for the manufacture of thin-walled components or combined with other manufacturing processes as a supplementary densification method. For RMI, its high-temperature melt is easy to damage the carbon fiber and seriously reduce the mechanical properties of the composite material.
[0005] In addition, the conventional PIP process mainly involves impregnating an organic precursor into a preform material, and then converting the organic precursor into an inorganic material through a pyrolysis process. This process can be repeated many times to form a composite material structure with a certain density in the matrix. However, this process often requires a long cycle to densify the preform, and repeated impregnation also makes it difficult to obtain a highly dense composite material. Summary of the invention
[0006] In order to solve the problems of low ultra-high temperature ceramic matrix content and long process cycle in the current preparation of fiber-reinforced ultra-high temperature ceramic matrix composites, the purpose of the present invention is to provide a fiber-reinforced ultra-high temperature ceramic matrix composite material with efficient and uniform introduction of ceramic matrix and a preparation method thereof. Through the preparation process of the present invention, high-performance fiber-reinforced composite materials with high ceramic content can be obtained, and the preparation is simple and efficient.
[0007] The present invention provides a method for preparing a fiber-reinforced ultra-high temperature ceramic-based composite material, comprising the following steps:
[0008] Step 1, using a water-soluble polymer as a dispersant, mixing ultra-high temperature ceramic powder and a solvent to prepare a slurry with a solid content of 25 to 45 vol%, and then wet-ball milling the slurry;
[0009] Step 2, subjecting the wet ball-milled slurry to magnetic stirring, and then immersing the carbon fiber preform in the slurry, performing vacuum slurry impregnation and applying ultrasonic vibration to obtain a green body;
[0010] Step 3: immersing the green body in a ceramic precursor, performing pressure impregnation and applying ultrasonic vibration, and then performing curing and cracking to obtain a fiber-reinforced ultrahigh temperature ceramic matrix composite material.
[0011] In an embodiment of the present invention, in step 1, the ultra-high temperature ceramic powder composition is one or more of zirconium boride, zirconium carbide, hafnium boride, hafnium carbide, hafnium nitride, tantalum boride, tantalum carbide, titanium boride, titanium carbide and silicon carbide; the particle size of the ultra-high temperature ceramic powder is 0.2 to 3 μm.
[0012] In an embodiment of the present invention, in step 1, the dispersant is one or more of polyethyleneimine, polyvinyl alcohol, polyvinyl butyral and polyvinyl pyrrolidone; the amount of the dispersant is 0.5-3wt% of the ultra-high temperature ceramic powder;
[0013] The solvent is one or more of ethanol, acetone and water.
[0014] In an embodiment of the present invention, in the step 1, the rotation speed of the wet ball milling is 250-400 r / min, the ball-to-material ratio is 5-10:1, and the ball milling time is 3-18 h.
[0015] In an embodiment of the present invention, in step 2, the carbon fiber preform is a 2D, 2.5D or 3D preform; and the thickness of the interface layer of the carbon fiber preform is 300 to 1200 nm.
[0016] In an embodiment of the present invention, in the step 2, the vacuum degree of the vacuum slurry impregnation is -0.05 to -0.098 MPa, and the impregnation time is 2 to 12 hours.
[0017] In an embodiment of the present invention, in step 2, the frequency of the ultrasonic vibration is 40-100 KHz, the time of the ultrasonic vibration is 60-180 min, and the water is changed every 5-10 min to ensure that the viscosity of the slurry during the immersion process is 0.2-15 Pa·s.
[0018] In an embodiment of the present invention, in step 3, the pressure of the pressurized impregnation is 0.5-2MPa, and the impregnation time is 2-12h; the frequency of the ultrasonic vibration is 40-100KHz, the time of the ultrasonic vibration is 60-180min, and the water is changed every 5-10min.
[0019] In an embodiment of the present invention, the step 3 is performed for at least 3 cycles; wherein the curing temperature is 100 to 300° C., and the curing time is 60 to 360 min;
[0020] The cracking temperature is 1100-1800° C., the cracking time is 60-180 minutes, and the cracking atmosphere is an inert atmosphere.
[0021] The present invention provides a fiber-reinforced ultra-high temperature ceramic-based composite material obtained by the above-mentioned preparation method.
[0022] Compared with the prior art, the process of the present invention is mainly as follows: first, ultra-high temperature ceramic slurry is obtained after wet ball milling; then, ultrasonic vibration is used to assist vacuum slurry impregnation, and the rheological properties of the slurry are regulated by ultrasonic vibration, so as to efficiently and uniformly introduce ultra-high temperature ceramic powder into the carbon fiber preform; then, the obtained green body is immersed in the ceramic precursor, pressurized impregnation is performed and ultrasonic vibration is applied, and finally, after curing and cracking, a densified fiber-reinforced ultra-high temperature ceramic matrix composite material is obtained. In the present invention, the vacuum slurry impregnation process is assisted by ultrasonic vibration, which is beneficial to improve the efficiency of introducing ultra-high temperature ceramic powder; and the vacuum slurry impregnation is assisted by ultrasonic vibration, and the combined process of ultrasonic vibration assisted pressure impregnation-cracking is combined to further improve the introduction efficiency and amount of ultra-high temperature ceramic powder in the fiber preform, thereby breaking through the problems of low efficiency and many cycle periods of ceramic precursor impregnation in the traditional PIP process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM image of Example 1 after ultrasonic-assisted vacuum slurry impregnation;
[0024] Figure 2 This is the SEM image of Comparative Example 1 after vacuum slurry impregnation. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those skilled in the art generally understand. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0026] The present invention provides a method for preparing a fiber-reinforced ultra-high temperature ceramic-based composite material, comprising the following steps:
[0027] Step 1, using a water-soluble polymer as a dispersant, mixing ultra-high temperature ceramic powder and a solvent to prepare a slurry with a solid content of 25 to 45 vol%, and then wet-ball milling the slurry;
[0028] Step 2, subjecting the wet ball-milled slurry to magnetic stirring, and then immersing the carbon fiber preform in the slurry, performing vacuum slurry impregnation and applying ultrasonic vibration to obtain a green body;
[0029] Step 3: immersing the green body in a ceramic precursor, performing pressure impregnation and applying ultrasonic vibration, and then performing curing and cracking to obtain a fiber-reinforced ultrahigh temperature ceramic matrix composite material.
[0030] By using the preparation method of the present invention, a high-performance fiber-reinforced composite material with a high ceramic content can be obtained, and the process is simple and the process cycle is short.
[0031] The embodiment of the present invention uses a certain proportion of ultra-high temperature ceramic powder, mixed with a water-soluble polymer dispersant and a solvent, to form a slurry with a certain rheological property. Among them, the ultra-high temperature ceramic powder component is preferably a mixture of one or more of zirconium boride (ZrB2), zirconium carbide (ZrC), hafnium boride (HfB2), hafnium carbide (HfC), hafnium nitride, tantalum boride (TaB2), tantalum carbide (TaC), titanium boride (TiB2), titanium carbide (TiC) and silicon carbide (SiC), for example, one or more of zirconium boride, hafnium boride, hafnium carbide, and silicon carbide.
[0032] The ultra-high temperature ceramic powder described in the embodiment of the present invention may be a conventional commercial product, with a purity of 99.5% or more and a particle size of preferably 0.2 to 3 μm. In addition, the dispersant is preferably one or more of water-soluble polymers (molecular weight may be 5000 to 50000) such as polyethyleneimine (PEI), polyvinyl alcohol (PVA), polyvinyl butyral (PVB) and polyvinyl pyrrolidone (PVP), further polyethyleneimine. Preferably, the amount of the dispersant is 0.5 to 3 wt % of the ultra-high temperature ceramic powder, and more preferably 1 to 2.5 wt %. The solvent may be one or more of ethanol, acetone and water (generally deionized water in the laboratory), and more preferably anhydrous ethanol. The embodiment of the present invention optimizes and regulates the rheological properties of the slurry, wherein the solid content of the ultra-high temperature ceramic powder is 25 to 45 vol %, more preferably 28 to 40 vol %, and more preferably 30 to 35 vol %.
[0033] Then, in the embodiment of the present invention, the prepared slurry is put into a ball mill for wet ball milling to mix the slurry evenly. The equipment for wet ball milling in the embodiment of the present invention is a ball mill commonly used in the art; the preferred ball milling speed is 250-400 r / min, the ball-to-material (mass) ratio can be 5-10:1, and the ball milling time is 3-18 hours, preferably 5-15 hours, and more preferably 6-10 hours.
[0034] In an embodiment of the present invention, the slurry obtained by the wet ball milling is magnetically stirred, and then the carbon fiber preform is immersed in the slurry for vacuum slurry impregnation, and ultrasonic vibration is applied at the same time to obtain a green body; the application of ultrasonic vibration in this step is mainly to prevent the sedimentation of the ultra-high temperature ceramic powder and affect the rheology of the slurry.
[0035] In the embodiments of the present invention, the carbon fiber preform is generally a workpiece formed by preforming the continuous carbon fiber of the reinforcing material into a desired shape by a setting agent or a weaving method, and can be a 2D, 2.5D or 3D preform. The discontinuous boundary between the fiber and the matrix of the preform usually has a layered structure, has good physical and chemical compatibility with the fiber and the matrix, and is called an interface layer; in some embodiments, the thickness of the interface layer of the carbon fiber preform can be 300 to 1200 nm.
[0036] The embodiment of the present invention adopts the process of ultrasonic vibration-assisted vacuum slurry impregnation, wherein the vacuum degree is preferably -0.05 to -0.098 MPa, more preferably -0.09 MPa, and the vacuum impregnation time can be 2 to 12 hours, preferably 5 to 10 hours; the frequency of ultrasonic vibration is preferably 40 to 100 KHz, more preferably 40 to 60 KHz, the ultrasonic vibration time can be 60 to 180 minutes, and the water is changed every 10 minutes to prevent the rapid rise of water temperature during the ultrasonic process from causing changes in the rheological properties of the slurry. In some embodiments, the ball-milled slurry is a slurry with rheological properties, and the shear stress is 1e -6 ~15e -6 MPa, shear rate 0.99~1.2s -1 , the viscosity is 0.2-15 Pa.s (obtained by conventional testing using a rotational rheometer). Further, the shear stress of the slurry after wet ball milling can be 4.5-6.4e -6 MPa, shear rate 0.99~1.11s -1 , viscosity is 4.8~5.4Pa.s.
[0037] The vacuum slurry impregnation process of the embodiment of the present invention improves the efficiency of introducing ultra-high temperature ceramic-based powders, wherein ultrasonic vibration avoids the sedimentation of ultra-high temperature ceramic powders, and regular water changes are performed to avoid rapid rise in water temperature and affect the rheological properties of the slurry. It can solve the problem of uneven distribution of ceramic powder particles in the fiber preform in the traditional slurry impregnation process.
[0038] After obtaining the green body impregnated with the vacuum slurry, the embodiment of the present invention immerses it in a ceramic precursor for pressurized impregnation and applies ultrasonic vibration. In the embodiment of the present invention, the ceramic precursor may be one of a zirconium boride precursor, a zirconium carbide precursor, a hafnium boride precursor, a hafnium carbide precursor, a tantalum boride precursor, a tantalum carbide precursor, a titanium boride precursor, a titanium carbide precursor, a hafnium nitride precursor, and a silicon carbide precursor, such as a SiC precursor, wherein the polymer is polycarbosilane (PCS). For example, the shear stress of the SiC precursor may be 0.64e -6 MPa, shear rate 1.6s -1 , viscosity is 0.05Pa.s.
[0039] Preferably, the pressure of the pressurized impregnation in the embodiment of the present invention is 0.5-2MPa, further 1-1.8MPa, and the time of the pressurized impregnation can be 2-12h, preferably 3-10h. At the same time, the frequency of the applied ultrasonic vibration can be 40-100KHz, the time of the ultrasonic vibration is preferably 60-180min, more preferably 60-120min, and the water is changed every 10min to prevent the rapid rise of water temperature during the ultrasonic process from causing changes in the rheological properties of the ceramic precursor.
[0040] Subsequently, the embodiment of the present invention can be cured at 100-300°C, and after 60-360 minutes, cracked in an inert atmosphere; the cracking temperature is preferably 1100-1800°C, and the cracking time is 60-180 minutes. The preferred embodiment of the present invention repeats the ultrasonic vibration assisted pressure impregnation, curing, and cracking process more than 3 times, such as 4-6 cycles, to obtain a fiber-reinforced ultra-high temperature ceramic matrix composite material that is efficiently and uniformly introduced into the ceramic matrix.
[0041] The embodiment of the present invention combines the ultrasonic vibration-assisted vacuum slurry impregnation and the ultrasonic vibration-assisted pressure impregnation-cracking process to densify the ceramic matrix, which can improve the introduction efficiency and amount of ultra-high temperature ceramic powder in the fiber preform. At the same time, the method of the present invention shortens the process cycle and is simple and easy to implement.
[0042] Accordingly, the embodiment of the present invention provides a fiber-reinforced ultra-high temperature ceramic-based composite material obtained by the preparation method as described above, wherein the ceramic matrix is uniformly introduced, has a high ceramic content, and has excellent properties such as bending strength.
[0043] In order to better understand the present invention, the content of the present invention is further illustrated below in conjunction with the examples, but the content of the present invention is not limited to the following examples. Unless otherwise specified, the various reagents and raw materials used in the present invention are all commodities that can be purchased from the market or products that can be prepared by recognized methods.
[0044] Example 1
[0045] Using 99% pure ZrB2 with a particle size of 2 μm and 500 nm SiC as raw materials (the volume ratio of ZrB2 to SiC is 4:1), 1 wt% of the raw material polyethyleneimine dispersant (molecular weight of 10,000) is added, and anhydrous ethanol is used as solvent to prepare a slurry, wherein the solid content of the raw material is 30 vol%; with a ball-to-material ratio of 5:1, wet ball milling at a speed of 300 r / min for 6 hours to prepare a mixed slurry, and the shear stress of the slurry obtained by ball milling is 5.3e -6 MPa, shear rate 1.01s -1 , viscosity is 5.1Pa.s.
[0046] The slurry obtained by the above wet ball milling is magnetically stirred; then, the 3D carbon fiber preform with an interface of 500nm is immersed in the slurry, vacuum slurry impregnation is performed and ultrasonic vibration is applied, the vacuum degree of vacuum slurry impregnation is -0.09MPa, the vacuum impregnation time is 10h, the frequency of ultrasonic vibration is 40KHz, the time of ultrasonic vibration is 60min, and the water is changed every 10min to prevent the rapid rise of water temperature during ultrasonic vibration from causing changes in the rheological properties of the slurry, and obtain the green body after ultrasonic vibration-assisted vacuum slurry impregnation.
[0047] The green body obtained above was immersed in SiC precursor (precursor is PCS) for pressure impregnation and ultrasonic vibration was applied. The shear stress of SiC precursor is 0.64e -6 MPa, shear rate 1.6s -1 , viscosity is 0.05Pa.s, pressure of pressurized impregnation is 1MPa, time of pressurized impregnation is 10h, frequency of ultrasonic vibration is 40KHz, time of ultrasonic vibration is 60min, and water is changed every 10min to prevent the rapid rise of water temperature during ultrasonic vibration from causing rheological changes of SiC precursor. Then, after curing at 160℃ for 3h, it is pyrolyzed at 1100℃ for 1h in Ar atmosphere, and the ultrasonic pressurized impregnation, curing and pyrolysis process is repeated 5 times to obtain a fiber-reinforced ultrahigh temperature ceramic matrix composite material, denoted as C f / ZrB2-SiC composite materials.
[0048] Income C f The content of ZrB2 in the ZrB2-SiC composite material is 29.3 vol%, the content of SiC is 35.1 vol%, the porosity is 7.2%, and the flexural strength is 380.3±20.1 MPa.
[0049] The porosity is tested by the Archimedes drainage method, and the bending strength is tested by the three-point bending strength test method, which are conventional tests in the art and are the same in the following embodiments.
[0050] Example 2
[0051] HfB2 with a purity of 99.5% and a particle size of 500 nm and HfC with a particle size of 500 nm were used as raw materials (the volume ratio of HfB2 to HfC was 4:1), 1 wt% of the raw material was added as a polyethyleneimine dispersant (molecular weight of 10,000), and anhydrous ethanol was used as a solvent to prepare a slurry, wherein the solid content of the raw material was 30 vol%; a ball-to-material ratio of 5:1 and a speed of 300 r / min were used to wet-mill for 6 hours to prepare a uniformly mixed slurry, and the shear stress of the slurry obtained by ball milling was 4.5e -6 MPa, shear rate 0.99s -1 , viscosity is 4.8Pa.s.
[0052] The slurry obtained after the above wet ball milling is magnetically stirred; then, the 3D carbon fiber preform with an interface of 500nm is immersed in the slurry, vacuum slurry impregnation is performed and ultrasonic vibration is applied, the vacuum degree of vacuum slurry impregnation is -0.09MPa, the vacuum impregnation time is 10h, the frequency of ultrasonic vibration is 40KHz, the time of ultrasonic vibration is 60min, and the water is changed every 10min to prevent the rapid rise of water temperature during ultrasonic vibration from causing changes in the rheological properties of the slurry, and obtain the green body after ultrasonic vibration-assisted vacuum slurry impregnation.
[0053] The green body obtained above was immersed in SiC precursor for pressure impregnation and ultrasonic vibration was applied. The shear stress of SiC precursor was 0.64e -6 MPa, shear rate 1.6s -1 , viscosity is 0.05Pa.s, pressure of pressurized impregnation is 1MPa, time of pressurized impregnation is 10h, frequency of ultrasonic vibration is 40KHz, time of ultrasonic vibration is 60min, and water is changed every 10min to prevent the rapid rise of water temperature during ultrasonic vibration from causing rheological changes of SiC precursor. Then, after curing at 160℃ for 3h, it is pyrolyzed at 1100℃ for 1h in Ar atmosphere, and the ultrasonic pressurized impregnation, curing and pyrolysis process is repeated 5 times to obtain C f / HfB2-HfC-SiC composite materials.
[0054] Income C f The content of HfB2 in the / HfB2-HfC-SiC composite material is 25.4vol%, the content of HfC is 6.2vol%, the content of SiC is 33.5vol%, the porosity is 8.4%, and the flexural strength is 390.4±23.6MPa.
[0055] Example 3
[0056] ZrB2 with a purity of 99% and a particle size of 2 μm was used as the raw material, 1.5 wt% of polyvinyl butyral dispersant (molecular weight of 20,000) was added to the raw material, and anhydrous ethanol was used as the solvent to prepare a slurry, wherein the solid content of the raw material was 35 vol%; the ball-to-material ratio was 5:1, and the speed was 300 r / min for 6 hours to prepare a uniformly mixed slurry, and the shear stress of the slurry obtained by ball milling was 6.4e - 6 MPa, shear rate 1.1s -1 , viscosity is 5.4Pa.s.
[0057] The slurry obtained by the above wet ball milling is magnetically stirred; then, the 2.5D carbon fiber preform with an interface of 600nm is immersed in the slurry, vacuum slurry impregnation is performed and ultrasonic vibration is applied, the vacuum degree of vacuum slurry impregnation is -0.09MPa, the vacuum impregnation time is 10h, the frequency of ultrasonic vibration is 40KHz, the time of ultrasonic vibration is 60min, and the water is changed every 10min to prevent the rapid rise of water temperature during ultrasonic vibration from causing changes in the rheological properties of the slurry, and obtain the green body after ultrasonic vibration-assisted vacuum slurry impregnation.
[0058] The green body obtained above was immersed in SiC precursor for pressure impregnation and ultrasonic vibration was applied. The shear stress of SiC precursor was 0.64e -6 MPa, shear rate 1.6s -1 , viscosity is 0.05Pa.s, pressure of pressurized impregnation is 1MPa, time of pressurized impregnation is 10h, frequency of ultrasonic vibration is 40KHz, time of ultrasonic vibration is 60min, and water is changed every 10min to prevent the rapid rise of water temperature during ultrasonic vibration from causing rheological changes of SiC precursor. Then, after curing at 160℃ for 3h, it is pyrolyzed at 1100℃ for 1h in Ar atmosphere, and the ultrasonic pressurized impregnation, curing and pyrolysis process is repeated 6 times to obtain C f / ZrB2-SiC composite materials.
[0059] Income C f The content of ZrB2 in the ZrB2-SiC composite material is 29.8 vol%, the content of SiC is 30.2 vol%, the porosity is 10.1%, and the flexural strength is 360.5±19.6 MPa.
[0060] Comparative Example 1
[0061] Using 99% pure ZrB2 with a particle size of 2 μm and 500 nm SiC as raw materials (the volume ratio of ZrB2 to SiC is 4:1), 1 wt% of the raw material polyethyleneimine dispersant (molecular weight of 10,000) is added, and anhydrous ethanol is used as solvent to prepare a slurry, wherein the solid content of the raw material is 30 vol%; with a ball-to-material ratio of 5:1, wet ball milling at a speed of 300 r / min for 6 hours to prepare a mixed slurry, and the shear stress of the slurry obtained by ball milling is 5.3e -6 MPa, shear rate 1.01s -1 , viscosity is 5.1Pa.s.
[0062] The slurry obtained by the above wet ball milling is magnetically stirred; then, the 3D carbon fiber preform with an interface of 500nm is immersed in the slurry for vacuum slurry impregnation. The vacuum degree of the vacuum slurry impregnation is -0.09MPa, and the vacuum impregnation time is 10h to obtain a blank after vacuum slurry impregnation.
[0063] The green body obtained above was immersed in SiC precursor, impregnated under pressure and subjected to ultrasonic vibration. The shear stress of SiC precursor was 0.64e -6 MPa, shear rate 1.6s -1 , viscosity 0.05Pa.s, pressure of pressurized impregnation 1MPa, time of pressurized impregnation 10h, frequency of ultrasonic vibration 40KHz, time of ultrasonic vibration 60min, and water change every 10min. Then, after curing at 160℃ for 3h, pyrolysis at 1100℃ for 1h in Ar atmosphere, the ultrasonic pressurized impregnation, curing and pyrolysis process were repeated 5 times to obtain C f / ZrB2-SiC composite materials.
[0064] Income C f The content of ZrB2 in the ZrB2-SiC composite material is 26.3vol%, the content of SiC is 33.2vol%, the porosity is 9.6%, and the flexural strength is 320.8±37.4MPa.
[0065] Comparative Example 2
[0066] Using 99% pure ZrB2 with a particle size of 2 μm and 500 nm SiC as raw materials (the volume ratio of ZrB2 to SiC is 4:1), 1 wt% of the raw material polyethyleneimine dispersant (molecular weight of 10,000) is added, and anhydrous ethanol is used as solvent to prepare a slurry, wherein the solid content of the raw material is 30 vol%; with a ball-to-material ratio of 5:1, wet ball milling at a speed of 300 r / min for 6 hours to prepare a mixed slurry, and the shear stress of the slurry obtained by ball milling is 5.3e -6 MPa, shear rate 1.01s -1 , viscosity is 5.1Pa.s.
[0067] The slurry obtained by the above wet ball milling is magnetically stirred; then, the 3D carbon fiber preform with an interface of 500nm is immersed in the slurry for vacuum slurry impregnation. The vacuum degree of the vacuum slurry impregnation is -0.09MPa, and the vacuum impregnation time is 10h to obtain a blank after vacuum slurry impregnation.
[0068] The green body obtained above was immersed in SiC precursor for pressure impregnation. The shear stress of SiC precursor was 0.64e -6 MPa, shear rate 1.6s -1 , viscosity 0.05Pa.s, pressure of pressurized impregnation 1MPa, time of pressurized impregnation 10h, then cured at 160℃ for 3h, cracked at 1100℃ for 1h in Ar atmosphere, repeated pressurized impregnation, curing, cracking process 5 times, obtained C f / ZrB2-SiC composite materials.
[0069] Income C f The content of ZrB2 in the ZrB2-SiC composite material is 24.5vol%, the content of SiC is 30.2vol%, the porosity is 13.6%, and the flexural strength is 290.3±35.8MPa.
[0070] Figure 1 This is a scanning electron microscope (SEM) image of Example 1 after ultrasonic-assisted vacuum slurry impregnation; Figure 2 This is a SEM image of comparative example 1 after vacuum slurry impregnation. As can be seen from the comparison, the ceramic matrix of the present invention is efficiently and uniformly introduced into the composite material.
[0071] It can be seen from the above embodiments that the embodiments of the present invention prepare high-performance fiber-reinforced composite materials with high ceramic content, and the preparation is simple and efficient. The embodiments of the present invention utilize ultrasonic vibration-assisted vacuum slurry impregnation process, which is beneficial to improve the efficiency of introducing ultra-high temperature ceramic-based powders; and through ultrasonic vibration-assisted vacuum slurry impregnation, combined with ultrasonic vibration-assisted pressurized impregnation-cracking combined process, the introduction efficiency and amount of ultra-high temperature ceramic powders in the fiber preform are further improved, thereby breaking through the problems of low ceramic precursor impregnation efficiency and multiple cycle periods in the traditional PIP process. Therefore, the method of the present invention has unexpected excellent effects and is suitable for large-scale promotion and application.
[0072] It should be noted that, for those skilled in the art, several improvements and modifications may be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a fiber-reinforced ultra-high temperature ceramic matrix composite material, characterized in that: The following steps are involved: Step 1, using a water-soluble polymer as a dispersant, mixing ultra-high temperature ceramic powder and a solvent to prepare a slurry with a solid content of 25 to 45 vol%, and then wet-ball milling the slurry; Step 2, subjecting the wet ball-milled slurry to magnetic stirring, and then immersing the carbon fiber preform in the slurry, performing vacuum slurry impregnation and applying ultrasonic vibration to obtain a green body; Step 3: immersing the green body in a ceramic precursor, performing pressure impregnation and applying ultrasonic vibration, and then performing curing and cracking to obtain a fiber-reinforced ultrahigh temperature ceramic matrix composite material.
2. The preparation method according to claim 1, characterized in that: In step 1, the ultra-high temperature ceramic powder component is one or more of zirconium boride, zirconium carbide, hafnium boride, hafnium carbide, hafnium nitride, tantalum boride, tantalum carbide, titanium boride, titanium carbide and silicon carbide; The particle size of the ultra-high temperature ceramic powder is 0.2-3 μm.
3. The preparation method according to claim 1, characterized in that: In step 1, the dispersant is one or more of polyethyleneimine, polyvinyl alcohol, polyvinyl butyral and polyvinyl pyrrolidone; the amount of the dispersant is 0.5-3wt% of the ultra-high temperature ceramic powder; The solvent is one or more of ethanol, acetone and water.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step 1, the rotation speed of the wet ball mill is 250-400 r / min, the ball-to-material ratio is 5-10:1, and the ball milling time is 3-18 h.
5. The preparation method according to any one of claims 1 to 3, characterized in that: In the step 2, the carbon fiber preform is a 2D, 2.5D or 3D preform; and the thickness of the interface layer of the carbon fiber preform is 300 to 1200 nm.
6. The preparation method according to claim 5, characterized in that: In the step 2, the vacuum degree of the vacuum slurry impregnation is -0.05 to -0.098 MPa, and the impregnation time is 2 to 12 hours.
7. The preparation method according to claim 6, characterized in that: In step 2, the frequency of the ultrasonic vibration is 40 to 100 KHz, the time of the ultrasonic vibration is 60 to 180 minutes, and the water is changed every 5 to 10 minutes to ensure that the viscosity of the slurry during the immersion process is 0.2 to 15 Pa·s.
8. The preparation method according to claim 7, characterized in that: In step 3, the pressure of the pressurized immersion is 0.5-2 MPa, and the immersion time is 2-12 hours; the frequency of the ultrasonic vibration is 40-100 KHz, the time of the ultrasonic vibration is 60-180 minutes, and the water is changed every 5-10 minutes.
9. The preparation method according to claim 8, characterized in that: The step 3 is performed for at least 3 cycles; wherein the curing temperature is 100 to 300° C. and the curing time is 60 to 360 minutes; The cracking temperature is 1100-1800° C., the cracking time is 60-180 minutes, and the cracking atmosphere is an inert atmosphere.
10. The fiber-reinforced ultra-high temperature ceramic-based composite material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for uniformly introducing ultrahigh-temperature ceramic component to braided three-dimensional carbon fibers with high content
CN108218455A
Preparation method of three-dimensional carbon fiber toughened ultrahigh-temperature ceramic-based composite material with high breaking work
CN108558422A
Cf / ZrB2-SiC ultrahigh-temperature ceramic matrix composite material of laminated structure and preparing method thereof
CN110204345A
Preparation method of particle-reinforced ultrahigh-temperature ceramic-based composite material
CN112645723A
Strong-ablation-resistant rare earth modified ultra-high-temperature ceramic-based composite material and preparation method thereof
CN113526972A